Le théâtre québécois à l’épreuve du conflit des codes : le cas Claude Gauvreau (1925-1971) - Novat, Astrid (Ponti/Ponts, 2024)
The development of Quebec theater is intrinsically linked to the history of its autonomy. Although numerous initiatives were put in place at the end of the 1950s, allowing for the development of a local repertoire, it became apparent that the French influence was an obstacle to its emergence. Numerous authors therefore set about creating plays whose aim was to translate a Quebec reality. If these new realist-influenced plays now assume a specular function in order to contribute to the creation of a national repertoire, it appears that the form itself evolves only slightly. If historiography often opposes national theater and modernity, it appears that certain authors such as Claude Gauvreau use formal innovation to propose a reflection on the particularity of Quebec culture.